Expression of OPN3 in lung adenocarcinoma promotes epithelial‐mesenchymal transition and tumor metastasis - Chao Xu (Thoracic Cancer, 2020)
Background Lung adenocarcinoma is the most common pathological lung cancer and an important cause of cancer‐related death. Metastasis is a major underlying reason for poor prognosis of lung adenocarcinoma. Opsin3 (OPN3), a member of the guanine nucleotide‐binding protein‐coupled receptor superfamily, has been identified to affect the apoptosis of hepatoma cells by modulating the phosphorylation of Akt and Bcl2/Bax. However, the expression and role of OPN3 in lung adenocarcinoma remains unclear. Methods Opsin3 expression in lung adenocarcinoma tissues was detected by western blot, qPCR, and immunohistochemistry. Changes in cell migration and invasion ability resulting from the change of OPN3 expression level were detected by wound healing and transwell migration assays. Changes in the markers of epithelial‐mesenchymal transformation were detected by western blot and qPCR. Results Opsin3 expression in lung adenocarcinoma tissues was higher than that in normal lung tissues. Patients with high expression of OPN3 had lower survival rates. Owing to overexpression of OPN3, the HCC827 cells showed enhanced invasion and migration ability in vitro. Upon decreasing the expression of OPN3, the invasion and migration ability of the A549 cells decreased. Conclusion Our study demonstrated for the first time that OPN3 gene enhanced the metastasis in lung adenocarcinoma, and its overexpression promoted epithelial‐mesenchymal transition. Key points A significant finding of the study was that OPN3 acted an oncogene in promoting lung adenocarcinoma metastasis. Our study complemented the research on the expression and function of OPN3 in lung adenocarcinoma.